Strategi Penggunaan Container dalam Meningkatkan Efisiensi Logistik Oleh PT. Salam Pacific Indonesia Lines Cabang Medan - Annisa Firdausi; Nurmaliana Sari Siregar (Asosiasi Riset Ilmu Manajemen dan Bisnis Indonesia, 2025)
Salam Pacific Indonesia Lines is a company included in the largest domestic shipping industry in the field of logistics and sea transportation services with a focus on inter-island container transportation in Indonesia using ships. This paper aims to determine how the container utilization strategy in improving logistics efficiency by PT. Salam Pacific Indonesia Lines Medan Branch. The process begins with selecting the right type of container, standardization and consolidation of cargo, integration of digital logistics systems, and optimization of routes and modes of transportation. In compiling this paper, the author applies several methods, including field studies or direct observations in the field, and library studies or literature reviews. The goal is to understand more deeply how PT. Salam Pacific Indonesia Lines Medan branch implements a container utilization strategy to improve efficiency in logistics activities. The obstacles faced in handling this are fleet and vehicle constraints, limited promotion and adjustment of application technology, traffic congestion, and weather and safety factors. In addition, inefficiencies in the distribution process, lack of good cooperation and coordination, and technological limitations are obstacles in optimizing container use. Good coordination can improve the service of goods delivery activities so that they can run smoothly, safely and efficiently.